Diseño de una máquina que mejore la producción de galletas para perros en la empresa Cookie Pets & Co. (2021)
This project presented the design of a machine that performs the manufacturing process of dog cookies from the kneading to the molding of the product, for this an analysis of the current situation of the process was made, then it was given step to define and evaluate the different alternative solutions for each of the systems that make up the machine to give solution to the proposed problem, the design of the machine was made taking into account the calculations and the selection of the mechanical parts that make up each system. Assembly, operation, safety and maintenance manuals were prepared, as well as the necessary manufacturing and assembly drawings. Finally, a financial and environmental evaluation was carried out to determine the feasibility of the project.